Expression Profiling and Cell Type Classification Analysis in Periodontitis Reveal Dysregulation of Multiple lncRNAs in Plasma Cells - Wu, Donglei; Zhou, Peng; Cao, Fengdi; Lin, Zhengshen; Liang, Defeng; Zhou, Xincai (Frontiers in Genetics, 2020)
Objective: Periodontitis is a chronic inflammatory disease with a downregulated immune response. The mechanisms of the immune response, especially regarding immune-related long non-coding RNAs (lncRNAs), in periodontitis remain unclear. This study aimed to analyze the immune cell landscapes and immune-related transcriptome expression in periodontitis. Materials and methods: The periodontitis-related microarray data set GSE16134 was downloaded from the Gene Expression Omnibus database. Then, the proportions of the infiltrated immune cell subpopulations were evaluated by Cell-type Identification By Estimating Relative Subsets Of RNA Transcripts (CIBERSORT). Differentially expressed immune-related genes (DEMGs) and lncRNAs were analyzed by the “limma” package in R software. Co-expression of DEMGs and lncRNAs in immune cell subpopulations was evaluated. Gene set enrichment analysis (GSEA) was performed to identify alterations in immune function through potential pathways. Results: Increased numbers of plasma cells were observed in periodontitis-affected tissues versus those of healthy tissues, while T cells were downregulated. A total of 51 DEMGs were identified, and 12 immune-related signaling pathways were enriched by GSEA, most of which were related to the stimulation and function of B cells and T cells. Only 3 differentially upregulated lncRNAs (FAM30A, GUSBP11 and LINC00525) were screened for the regulation of the immune response. Besides, the level of lncRNAs (FAM30A, GUSBP11 and LINC00525) expression were positively correlated with the fraction of plasma cells in periodontitis. Conclusion: The discovery of differentially expressed immune-related transcriptomes in periodontitis lesions helps to explain the regulation of the immune mechanism in the development of periodontitis.